'Modern' forms of energy in the cottages and farms of Rural England, 1920–1960. Issue 1 (2nd January 2018) - Sayer, Karen A.
ABSTRACT: The modernisation of farming became a key policy issue in Britain after the Second World War, and the (more) efficient use of energy was seen as key to that process because of labour shortages. Traditionally, farms had been organised to make the best use of energy around the farm, be that energy human, animal, or mechanical, or (latterly) derived from off-farm fuels. The apparent crisis in the availability of human labour therefore led to propositions that labourers be encouraged to stay on the land, by improvements to housing and rural infrastructure, and that farms use new forms of energy, particularly electricity. Analysis of a range of sources, such as autobiographies, advertising literature, films, advisory texts, cash books, and social survey data, shows that, despite the political rhetoric, there was a high degree of continuity in energy consumption, however, that this was multiform and that change was far from linear, even as a range of fuels (paraffin, calor gas, petrol, diesel, TiVO), all selling themselves as 'Modern', came into use. Analysis shows that there were multiple, overlapping, and sometimes competing, rural 'modernities' in Britain 1920–1960.